Analyzing Brand Loyalty Drivers Among Generation Z Gamers - Sarita, Monika Claudia; Dewi, Cynthia Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2024)
The advancement of digital technology has profoundly altered societal lifestyles, particularly impacting Generation Z or iGeneration, who have adeptly navigated digital technologies since early childhood. Concurrently, online gaming, exemplified by Genshin Impact, has emerged as a pivotal component of this generation's social life. The fluctuating popularity of Genshin Impact in 2022 underscores shifting preferences and dynamics within online gaming. This research aims to analyze factors influencing brand loyalty within this context. The study surveyed 150 Genshin Impact players from Java Island, employing quantitative methods with primary data and utilizing Smart PLS 4.0 for data analysis. Findings indicate that electronic word of mouth (EWOM) does not directly influence brand loyalty, while online communities and online advertisements positively impact it. Brand image mediates the relationship between EWOM and brand loyalty. These insights are expected to assist the gaming industry in enhancing brand loyalty strategies. By understanding these dynamics, stakeholders can better align their marketing efforts with the evolving preferences of Generation Z, ensuring sustained engagement and loyalty in the competitive digital landscape